Penerapan Pendekatan Arsitektur Memorabilia Dalam Perancangan Museum Emporium Sedayulawas, Kabupaten Lamongan - Permatasari, Tiara; Santoso, Joko; Bintarjo, Benny (SADE : Jurnal Arsitektur, Planologi dan Teknik Sipil, 2024)
Indonesia has many islands in every region, both provinces/cities and districts. It is not surprising that each region in Indonesia has its own historical value in the formation of that region. Especially in Lamongan district, specifically in Sedayulawas, which has historical value during the emporium era which was one of the trade centers on the Indonesian spice route. so that there are relics in the form of objects, artifacts or stories that must be looked after in order to be preserved. This is used as a form of commemorating the existence of a very important historical heritage. The design of the Sedayulawa Emporium Museum is expected to be a place to care for, protect and collect historical objects and stories. The design of this museum will use a memorabilia architecture approach which in this case is able to create a museum environment by combining historical aspects so that it will form a sense of plan which is the embodiment of the impression of space and its function from a relationship of ontology and representation. This research uses a qualitative description method with data analysis using primary and secondary data. The results of this research will apply the form of buildings in the form of memorabilia taken from star anise flowers as one of the bases for designing a museum that is related to the historical values ​​that existed during the emporium period in Sedayulawas, Lamongan Regency. This star anise flower will later undergo a change in shape or transformation to be used as a museum building for the Sedayulawas emporium in Lamongan district. Kata kunci: History, Memorabilia, Emporium, Sedayulawas, Lawang Flowers